Chemopreventive effect of hesperidin, a citrus bioflavonoid in two stage skin carcinogenesis in Swiss albino mice - Mathipi Vabeiryureilai; Khawlhring Lalrinzuali; Ganesh Chandra Jagetia (Heliyon, 2019)
The cancer-protective ability of hesperidin was investigated on 7, 12-dimethylbenz[a]anthracene (DMBA) and 12-O-tetradecanoyl phorbol-13-acetate (TPA)-induced skin carcinogenesis in Swiss albino mice. Topical application of DMBA+TPA on mice skin led to 100% tumour incidence and rise in average number of tumours. Administration of different doses of hesperidin (HPD) before (pre) or after (post) and continuous (pre and post) DMBA application significantly reduced tumour incidence and average number of tumours in comparison to DMBA+TPA treatment alone. Topical application of DMBA+TPA increased oxidative stress as shown by significantly increased TBARS values and reduced glutathione contents, and glutathione-S-transferase, superoxide dismutase and catalase activities. Hesperidin treatment significantly reduced TBARS values and elevated glutathione concentration and glutathione-S-transferase, superoxide dismutase and catalase activities in the skin/tumors of mice treated with HPD+DMBA+TPA, HPD+DMBA+TPA+HPD or DMBA+TPA+HPD when compared to DMBA+TPA application alone. The study of molecular mechanisms showed that hesperidin suppressed expression of Rassf7, Nrf2, PARP and NF-κB in a dose dependent manner with a maximum inhibition at the level of 300 mg/kg body weight hesperidin. In conclusion, oral administration of hesperidin protected mice against chemical carcinogenesis by increasing antioxidant status, reducing DMBA+TPA induced lipid peroxidation and inflammatory response, and repressing of Rassf7, Nrf2, PARP and NF-κB levels.